A Study on the Influence of Various Factors in the Implementation of the E-Procurement System in Ngada Regency, East Nusa Tenggara - Arnolda Deru; Wateno Oetomo; Risma Marleno (LPPM of NAROTAMA UNIVERSITY, 2025)
The procurement of goods and services was previously conducted manually or conventionally. Presidential Regulation No. 54 of 2010, which replaced Presidential Decree No. 80 of 2003, formally contained the objective of e-procurement in the procurement of government goods/services for the first time. Neither the committee nor the providers of goods/services readily accepted the newly implemented system. The success of the e-procurement program is highly determined by the human factor. User readiness to accept the technology is the key to successful implementation, because their response will determine whether this technology succeeds or fails. This study uses mixed methods and aims to obtain empirical evidence about the influence of human resource competence, infrastructure, and supervision factors in the implementation of the e-Procurement system, as well as to provide strategic recommendations for improving the implementation of the e-Procurement system in Ngada Regency. The research sample consisted of 39 employees of the Goods and Services Procurement Section of Ngada Regency, selected using the saturated sampling technique within the nonprobability sampling method. Data was collected through questionnaire surveys and interviews, then analyzed using Smart Partial Least Square 3.2. The results of this study revealed that human resource competence, infrastructure, and supervision have a significant influence on the implementation of the e-Procurement system in Ngada Regency. Improvement in these three factors can enhance the success of the e-Procurement system implementation. Some recommended strategies to improve the implementation of the e-Procurement system are to conduct education and training, provide internet networks and backup servers through the Department of Information and Communication, carry out socialization to involve the public in monitoring, increase evaluation transparency by adding an evaluation column on the Electronic Procurement Institution (LPSE) website, conduct routine audits, and issue regulations regarding the implementation of e-audit in the process of procuring goods/services.